2020
DOI: 10.3390/nano10061164
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polysaccharides’ Molecular Structure on the Antibacterial Activity and Cytotoxicity of Green Synthesized Composites Based on Silver Nanoparticles and Carboxymethyl-Cellulose

Abstract: In this paper we report on the influence of polysaccharides’ molecular structure on the antibacterial activity and cytotoxicity of composites based on silver nanoparticles (AgNPs) immobilized into carboxymethyl-cellulose (CMC). These composites were green synthesized from the reduction of silver ions into aqueous solutions of the polysaccharide, using CMC with different degree of substitution (DS) and molecular weight (Mw). The composites were characterized by transmission electron microscopy (TEM), as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 45 publications
1
6
0
1
Order By: Relevance
“…[34][35][36][37] Previously few studies reported the synthesis of CMC fabricated silver NPs through chemical reduction methods. 38,39 However, there is no study available on the decoration of silver NPs with CMC via green route using Syzygium aromaticum buds extracts. In addition, no study reported the pharmacological and cytotoxic activities of CMC-based silver NPs.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37] Previously few studies reported the synthesis of CMC fabricated silver NPs through chemical reduction methods. 38,39 However, there is no study available on the decoration of silver NPs with CMC via green route using Syzygium aromaticum buds extracts. In addition, no study reported the pharmacological and cytotoxic activities of CMC-based silver NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Composites of CMC of different degree of substitution (DS) and molecular weight (Mw) containing stabilized AgNPs were green synthesized from the reduction of Ag + into aqueous solutions of the polysaccharide by using chemical method. Experimental evidence suggests that particle size distribution and morphology of AgNPs change according to the quantity of silver nitrate added to the reaction, as well as the DS and Mw of Na‐CMC used for composites preparation 12 …”
Section: Introductionmentioning
confidence: 99%
“…Even if they possess remarkable therapeutic effects and intrinsic biocompatibility, relentless efforts were done to maximize the bioactivity of AgNPs and improve their stability. In this respect, a wide variety of capping agents and surface coatings were successfully evaluated, including inorganic or organic, natural or synthetic materials [ 25 , 26 , 27 , 28 ].…”
Section: ⧉ Introductionmentioning
confidence: 99%